2020
DOI: 10.1042/bsr20201573
|View full text |Cite
|
Sign up to set email alerts
|

miRNA-1183-targeted regulation of Bcl-2 contributes to the pathogenesis of rheumatic heart disease

Abstract: To determine whether up-regulation of miR-1183 targeting the gene for anti-apoptotic factor, B cell lymphoma-2 (BCL-2) contributes to apoptosis in patients with rheumatic heart disease (RHD). Peripheral blood samples were isolated for miR-1183 characterization. The function of miRNA-1183 in RHD using miRNA mimic on PBMCs and THP-1 cell models. The binding of miR-1183 and Bcl-2 gene was confirmed by luciferase activity test.We also measured expression levels of BCL-2 in heart valve tissue from patients with RHD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 20 publications
1
5
0
1
Order By: Relevance
“…In addition to our microarray findings, it was recently published that Bcl2 is a direct molecular target of miR-1183 in rheumatic heart disease [74]. In our dataset BCL2 and associated anti-apoptotic pathways were not significantly regulated, but its interaction partner BNIP3 was down-regulated.…”
Section: Downstream Targets Of Mir-1183 and Cardiac Functional Effectssupporting
confidence: 59%
“…In addition to our microarray findings, it was recently published that Bcl2 is a direct molecular target of miR-1183 in rheumatic heart disease [74]. In our dataset BCL2 and associated anti-apoptotic pathways were not significantly regulated, but its interaction partner BNIP3 was down-regulated.…”
Section: Downstream Targets Of Mir-1183 and Cardiac Functional Effectssupporting
confidence: 59%
“…This may explain, at least in part, why LNA-antimiR-34a treatment in the current study did not regulate several miR-34a targets genes known to contribute to cardiac protection including Bcl2, Pnuts, Sirt1, Vegfa and Vegfb. For example, of the upregulated miRNAs described in previous diabetic studies, a number including miR-195, miR-483-3p, miR-210, miR-451, miR-181c, miR-1183, miR-145, miR-199, miR-137 and miR-499 have been shown to regulate mRNAs that are recognized targets of miR-34a including Bcl2 and Sirt1 [27,[50][51][52][53][54][55][56][57][58] (Figure 7B). It is therefore probably not surprising that in a setting of diabetes in which multiple miRNAs are upregulated and targeting the same mRNAs, inhibiting miR-34a alone had no significant impact on the regulation of some target genes (Figure 7B).…”
Section: Discussionmentioning
confidence: 76%
“…However, more studies are needed on miRNA sequencing and quantitative reverse transcription-PCR analysis of miRNA expression levels (17). In another study of RHD, miR-1183 was demonstrated to be differentially expressed showing that significantly higher expression levels of miR-1183 through regulation of the antiapoptotic protein, BCL-2, might affect myocardial apoptosis and remodeling (18).…”
Section: Host Genetic Susceptibilitymentioning
confidence: 99%
“…RHD continues to be an important cause of mortality and disability and yet remains a neglected disease (6)(7)(8). While there is strong evidence linking RHD to poor socio-economic (9, 10) and environmental conditions (11,12), the underlying pathogenesis, particularly the reasons for host susceptibility ( [13][14][15][16][17][18] and bacterial rheumatogenicity (19,20), remain poorly understood.…”
Section: Introductionmentioning
confidence: 99%